From the Sea to Anticancer Therapy - Russo, P.; Nastrucci, C.; Cesario, A. (Current Medicinal Chemistry, 2011)
Discovery, isolation, characterisation and pre-clinical and clinical trials of plant- or animal-derived drugs displaying pharmacological activities continue to develop and enlarge. Cancer chemotherapy is one of the most promising areas for these drugs. Since a very long time, nature has been an attractive source of potential medicinal agents for human use. The deep sea is becoming a novel and potently appealing source for new drugs, as well as shallow waters. This interest is mainly related to the terrific chemical diversity found in the vast number of plants and animal species, as well as in the microbial world. During the evolution, a rich source of biologically active compounds is developed in the depths of the sea, often reflecting ecological adaptation. Most of them (toxins) are developed to allow survival and flourishing acting against predators and parasites. Recent progress in Scuba diving, hitech/biotechnological and procedural advances in structure clarification, organic synthesis and biological assay determined the characterisation and preclinical/clinical evaluation of novel anticancer drugs. The aim of this review is to provide a description of their discovery, mode of action and clinical application.
Keywords: clinical trial